Media Komunikasi Pelayanan Publik Berbasis Website (Studi Kasus Bidang Penataan Ruang DPUPR Kota Serang) - Ardian Havidani; Titi Stiawati; Ipah Ema Jumiati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Public communication in the digital era is not only the ability to speak or communicate in public spaces but also how digital media becomes a communication space that can influence other people. This can make it easier for the community to obtain reliable and accurate information that supports the goals of developing urban facilities and infrastructure and providing maximum service to the community. This research focuses on how the role of website-based communication media. The Serang City Spatial Planning Information System (Simtaru) belongs to the Spatial Planning Division of the Public Works and Spatial Planning Office of Serang City as a public service communication medium. The city of Serang is capital of the province of Banten, has experienced very rapid development has changed the color of Serang City. At present, the need for information on spatial planning in Serang City is very much needed, both for the community and business people. This study uses a descriptive qualitative approach a case study (case study). The communication functions of high-tech communication media in conveying reliable and efficient information greatly facilitate the community and business actors. Serang City's Simtaru (Spatial Planning Information System) is experiencing obstacles, namely the lack of digital literacy for the community, limited human resources, and unstable network connections. Development of Simtaru as a database for spatial planning data and other cross-sections such as disaster data and infrastructure.